2021 American College of Rheumatology Guideline for the Treatment of Juvenile Idiopathic Arthritis: Recommendations for Nonpharmacologic Therapies, Medication Monitoring, Immunizations, and Imaging. Issue 4 (1st March 2022) - Onel, Karen B.; Horton, Daniel B.; Lovell, Daniel J.; Shenoi, Susan; Cuello, Carlos A.; Angeles‐Han, Sheila T.; Becker, Mara L.; Cron, Randy Q.; Feldman, Brian M.; Ferguson, Polly J.; Gewanter, Harry; Guzman, Jaime; et al.
Abstract : Objective: To provide recommendations for the management of juvenile idiopathic arthritis (JIA) with a focus on nonpharmacologic therapies, medication monitoring, immunizations, and imaging, irrespective of JIA phenotype. Methods: We developed clinically relevant Patient/Population, Intervention, Comparison, and Outcomes questions. After conducting a systematic literature review, the Grading of Recommendations Assessment, Development and Evaluation approach was used to rate the quality of evidence (high, moderate, low, or very low). A Voting Panel including clinicians and patients/caregivers achieved consensus on the direction (for or against) and strength (strong or conditional) of recommendations. Results: Recommendations in this guideline include the use of physical therapy and occupational therapy interventions; a healthy, well‐balanced, age‐appropriate diet; specific laboratory monitoring for medications; widespread use of immunizations; and shared decision‐making with patients/caregivers. Disease management for all patients with JIA is addressed with respect to nonpharmacologic therapies, medication monitoring, immunizations, and imaging. Evidence for all recommendations was graded as low or very low in quality. For that reason, more than half of the recommendations are conditional. Conclusion: This clinical practice guideline complements the 2019 American College of Rheumatology JIA and uveitis guidelines, which addressed polyarthritis, sacroiliitis, enthesitis, and uveitis, and a concurrent 2021 guideline on oligoarthritis, temporomandibular arthritis, and systemic JIA. It serves as a tool to support clinicians, patients, and caregivers in decision‐making. The recommendations take into consideration the severity of both articular and nonarticular manifestations as well as patient quality of life. Although evidence is generally low quality and many recommendations are conditional, the inclusion of caregivers and patients in the decision‐making process strengthens the relevance and applicability of the guideline. It is important to remember that these are recommendations. Clinical decisions, as always, should be made by the treating clinician and patient/caregiver.